AESTHETICS AND JUDGMENT: “WHY KANT GOT IT RIGHT” - Kyndrup, Morten (The Nordic Journal of Aesthetics, 2018)
The article argues that although all scholars within aesthetics basically know and recognize it, there is a tendency in many of its traditions to forget or to underestimate the importance of the aesthetic judgment. With Thierry de Duve’s short paper “Why Kant got it Right” as its point of departure, this importance is discussed. Not only its importance in aesthetic relations and to aesthetics as a discipline, but also in a broader sense, through the contribution to the overall social cohesion of society, offered by aesthetic judgments. All judgments are pronounced as-if a shared scale of aesthetic preferences did exist (which it does not). Judgments are addressed to communities, to the notion of a joint “we”, and thus they do participate in the creation and the maintenance of the social as such. Also professional aesthetic critique, including art critique, should be aware of that, since even historically achieved differentiations and divisions of labour may be lost again if not being developed and kept up to date.